PENGARUH EDUKASI BAHAYA SAMPAH PLASTIK TERHADAP PENGETAHUAN DAN SIKAP SISWA SDN SERANG 17 - Rian Azhar Ramadhan; Anna Maria Oktaviani; Lailatul Azkia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Plastic waste is an environmental problem that has a serious impact on ecosystemsand human health. The low awareness of elementary school students towardsplastic waste management shows the importance of environmental education froman early age. This study aims to analyze the influence of plastic waste hazardeducation on the knowledge and attitudes of SDN Serang 17 students. The studyused a quantitative approach with a quasi-experimental pre-test post-test controlgroup design. The research subjects consisted of students of SDN Serang 17 whowere divided into experimental groups and control groups. The research instrumentsare in the form of knowledge questionnaires and attitude questionnaires that havebeen validated. The experimental group was given education on the dangers ofplastic waste through interactive learning, while the control group followed the usuallearning. The results showed a significant increase in students' knowledge andattitudes in the experimental group compared to the control group. Thus, educationon the dangers of plastic waste is effective in increasing understanding and formingattitudes of caring for the environment in elementary school students.